Pengaruh Pelayanan Akademik, Fasilitas dan Kinerja Kampus terhadap Kepuasan Mahasiswa di Kabupaten Purwakarta - Azzam Waliyyul Alam3; Osep Hijuzaman; Sylviani, Yuli; Muhammad Nugrah Nopiasadi (Jurnal Teknologika, 2024)
The aim of this research is to analyze the influence of academic services, facilities and campus performance on student satisfaction. The method used in this research is Structural equation modeling (SEM). By distributing questionnaires to students in Purwakarta Regency. The population in this study was 32,134 people with a sample of 203 people (7% of the population). The results of this research showed no influence of academic services on student satisfaction; Likewise, campus performance has no influence on student satisfaction and campus facilities have no influence on student satisfaction.